The role of linguistics in teaching the Arabic language, an applied study on Laghti book (KSA) - Siddig, Ahmed Hussien Bilal (Journal of Curriculum and Teaching Methodology, 2022)
The research dealt with the role of linguistics in the teaching of Arabic language, with the application of (Laghti book) for the first three years of primary school in Saudi Arabia. The researcher divided the research into: a theoretical section dealing with the recognition of linguistics, theories, and modern linguistic curricula, which benefited educators in the curricula of the Arabic language, while the applied section, including the definition of my language book, and to identify aspects of the use of theories and linguistic approaches in it. The researcher used the descriptive analytical method in this research cause it suitable to this study, it describes the linguistic phenomenon and analyzes it. The research concluded a number of results: -Linguistics provide the accurate description of the language through theories and scientific methods controlled, which makes it easier for educators to benefit from them in the implementation of curricula in the language. -The authors of (Laghi book) have benefited from the structural, inductive, deductive and communicative approach in my language book.